The Rolling Stone jazz record guide - Swenson, John. (New York Rolling Stone Press, 1985)
In the sixty-odd years that jazz has been recorded, hundreds of books have attempted to define the music and the musicians who played it. But until now jazz has laced a basic and comprehensive reference work keyed to the central unit of consumption.
Keywords: Art